Processes Influencing Autocompaction Modulate Coastal Wetland Surface Elevation Adjustment With Sea-Level Rise - Rogers, Kerrylee; Saintilan, Neil (Frontiers in Marine Science, 2021)
The fate of coastal wetlands and their ecosystem services is dependent upon maintaining substrate elevations within a tidal frame that is influenced by sea-level rise. Development and application of morphodynamic models has been limited as few empirical studies have measured the contribution of key processes to surface elevation change, including mineral and organic matter addition, autocompaction of accumulating sediments and deep subsidence. Accordingly, many models presume that substrates are in equilibrium with relative sea-level rise and the composition of substrates are relatively homogenous. A 20-year record of surface elevation change and vertical accretion from a large tidal embayment in Australia coupled with analyses of inundation frequency and the character of sediments that have accumulated above mean sea level was analysed to investigate processes influencing surface elevation adjustment. This study confirms the varying contribution of addition, decomposition and compression of organic material, and mineral sediment consolidation, resulting in autocompaction that is proportional to the overburden of accumulating sediments. These processes operate concurrently and are influenced by sediment supply and hydrodynamic energy. Vertical accretion was linearly related to accommodation space. Surface elevation change was related to vertical accretion and substrate organic matter, indicated by carbon storage above mean sea level, and conformed to models that initially increase and then decrease as accommodation space diminishes. Rates of surface elevation change were largely found to be in equilibrium with sea-level rise measured at the nearest tide gauge, which was estimated at 3.5 mm y-1 over the period of measurements. As creation of new accommodation space with sea-level rise is contrary to the longer-term history of relative sea-level stability in Australia since the mid-Holocene, striking stratigraphic variation arises with deeper sediments dominated by mineral sands and surficial sediments increasingly fine grained and having higher carbon storage. As the sediment character of substrates was found to influence rates of surface elevation gain, we caution against the unqualified use of models derived from the northern hemisphere where substrates have continuously adjusted to sea-level rise and sediment character is likely to be more homogenous.